Exploring the prospects of Calotropis gigantea as a sustainable source of fiber and cellulose - Lia Handayani; Sri Aprilia; Nasrul Nasrul; Muhammad Roil Bilad (AGROINTEK, 2025)
C. gigantea (CG) is a shrub that thrives in highlands with intricate limestone soils and coastal regions. Apart from the bark, the fruit's interior also contains fine fibers with exceptional potential as a fiber material. The abundant availability of this plant, coupled with the manual fiber extraction process, renders it an affordable and promising fiber source for various applications. This paper aims to explore the research progress on the coastal wild plant C.gigantea as a biomaterial, focusing on its utilization as fiber, cellulose, cellulose nanocrystals, and their applications. The study highlights the potential of C.gigantea in various fields, emphasizing its value as a sustainable resource for advanced material development and innovative applications. The method employed in this study involved collecting research findings from various sources, including reputable international journals and accredited national journals, published within the last 10 years. This approach ensures the inclusion of up-to-date and high-quality studies, providing a comprehensive overview of the topic. Numerous studies have delved into CG plant-based fibers and cellulose nanocrystals (CNCs) as viable solutions to provide raw materials for natural polymer applications. Research endeavors persist in the quest for new natural resources possessing suitable physical, chemical, and mechanical properties to supplant synthetic fibers. These endeavors aim to unveil novel cellulosic materials applicable across diverse fields, particularly in composite material production. CG stands out as an alternative natural fiber endowed with distinctive characteristics, notably its hollow fiber structure, contributing to its low-density nature and excellent thermal insulation properties. Its incorporation as a composite material enhances the overall physical and mechanical properties of the composite. This article presents a concise overview of the unique attributes of CG (bark and seedpod fibers) and their applications, both as cellulose and reinforcement materials.